Young foreign women in prison: A case study in Malaga prison - Cerezo Anabel I.; Izco María (Temida, 2019)
The aim of this paper is to present the results of the research on the reality that young migrant women face in prison, trying to analyze whether they, judging by their own speech, consider themselves victims of some sorts of discrimination in Malaga’s prison. The main objective is to get to know the previous history of women before entry to prison, their criminal experience, experience in the judicial process and their daily activities in the penitentiary centre, as well as the treatment received by the prison staff. In addition, the paper tries to explain the expectations for the future of these young women after their release. The final conclusions reflect a very complicated situation for women living in Malaga prison, especially when factors such as age and migration are also involved.